ACHIEVING OF SUSTAINABLE ECONOMIC GROWTH AS A RESULT OF REDUCING INFLATION IN THE COUNTRY (Web of Discoveries: Journal of Analysis and Inventions, 2024)
This article explores the pivotal role of inflation elimination in driving sustainable economic growth within the context of Uzbekistan. Inflation, a persistent challenge for the nation's economy, has hindered consumer purchasing power, investment confidence, and overall economic stability. By examining the potential benefits of inflation eradication, this abstract sheds light on how Uzbekistan can pave the path towards sustained prosperity. Through meticulous analysis of the impact of inflation on consumer behavior, investment patterns, and international competitiveness, it underscores the necessity of adopting robust policy measures. The abstract emphasizes the importance of coordinated efforts from policymakers, central banks, and other stakeholders to implement effective monetary, fiscal, and structural reforms. By prioritizing inflation elimination, Uzbekistan can create an environment conducive to long-term economic growth, job creation, and enhanced living standards for its citizens.